The learner's Kanji dictionary = Kammei Kan-Ei jukugo jiten - Spahn, Mark; Hadamitzky, Wolfgang (C.E. Tuttle Co., 1998)
The purpose of this Learner's Kanji Dictionary is to offer a handy and easy-to-use Japanese language tool to look up the readings and meanings of Japanese words and names written with Chinese characters (kanji)